Effectiveness of CO2 laser in removal of papillary gingival hyperplasia - Sabrina Kívia Correia Gama; Fernando Antônio Lima Habib; Antônio Luiz Barbosa Pinheiro; Telma Martins de Araújo (Dental Press Editora, 2012)
INTRODUCTION: Laser applications have increased in a variety of dental procedures, especially in surgeries of soft tissues. Radiation is not invasive and is very well tolerated by tissues. CO2 laser acts in small vessels promoting blood coagulation, making it possible to work in a controlled way. Patients undergoing fixed orthodontic therapy often present injuries of gingival hyperplasia, originating esthetical and functional problems. OBJECTIVE: This study aimed at evaluating the CO2 laser effectiveness in removal of hyperplasia lesions in gingival papilla regions of patients with fixed orthodontic appliances. For this, ten patients were chosen and in these 75 teeth with gingival hyperplasia were identified. Measures from the papilla to incisal edge were performed with the use of a digital caliper. Besides that, the individuals were submitted to previous examinations to the surgical procedure with laser: Full blood count, blood coagulation profile and fasting blood glucose. After this, patients were submitted to the surgery for lesion removal, carried out at the Laser Center of FOUFBA, utilizing a CO2 laser machine (Sharplan 20C, Tel Aviv, Israel). RESULTS: It was showed that laser provided a significant increase (p<0,001) in the distance from the papilla to the incisal edge of the teeth, with no tissue contraction, aspects which were maintained for over two months. CONCLUSION: It can be concluded that CO2 laser has proved to be effective in removal of papillary gingival hyperplasia lesions.